Eksplorasi Etnomatematika Pada Permainan Tradisional Kelereng Di Kelurahan Bahagia, Babelan, Bekasi - Huri Suhendri; Rita Ningsih (Jurnal Derivat: Jurnal Matematika dan Pendidikan Matematika, 2023)
Abstract : This study aims to identify and describe ethnomathematics in the traditional game of marbles in the Happy Village, Babelan District, Bekasi Regency, West Java. The research method used is ethnomathematics with the object of research being the traditional game of marbles. The data sources in this study consisted of: the research object, namely marbles games, sources, namely 3 elders, and related documents discussing marbles games. Data collection techniques are carried out through: observation, interviews, and documentation. Based on the research results obtained and data analysis, it is concluded that there are mathematical concepts in the game of marbles, namely: the concept of geometric shapes in the shape of marbles, the concept of flat geometry and trigonometry in the shape of the game area of ​​marbles, and the concept of opportunity and integer arithmetic operations in the implementation marble game..  Keywords: Ethnomatematics, Traditional Games, Marbles, Babelan Village.